Trade-off among Mechanical Properties and Energy Consumption in Multi-pass Friction Stir Processing of Al 7075-T651 Alloy Employing Hybrid Approach of Artificial Neural Network and Genetic Algorithm - Bazaz, Shahin Hassanzadeh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: Friction Stir Processing (FSP) is a solid state and thermomechanical processing technique that modify and improve the microstructural and mechanical properties of the material to achieve better performance in less time, using a simple and inexpensive tool and low production cost. Processed zone contains modified mechanical properties, fine grained, equaled and homogeneous microstructures. Discussions about efficient use of energy and expense have become more frequent in many sectors of industry. During manufacturing processes, power consumption of components and potential for savings can be evaluated and measures can be defined for the efficient use of energy. In the present work, FSP was applied on the Aluminum 7075-T651 alloy sheet. Application of multi-objective multivariable genetic optimization in FSP was presented. A trade-off among various mechanical properties of an aerospace alloy and energy consumed during FSP was sought out. At first, the experimental data regarding the elongation, tensile strength, hardness and the consumed electrical energy with respect to various spindle rotational speed and feed rate of FSP were measured. Then an Artificial Neural Network-based approximation approach was used to approximate the value of measured data during the Genetic Optimization. The properties like elongation, tensile strength and hardness were maximized while the cost of consumed electrical energy was minimized. Keywords: Friction Stir Processing; Al7075; Multi-objective; Genetic Algorithm; Optimization; Artificial Neural Networks. ………………………………………………………………………………………………………………………… ÖZ: Sürtünme karıştırma işlemi (FSP) basit ve masrafsız araçlar kullanarak, üretim maliyeti az olan ve kısa sürede daha iyi bir performans elde etmek için kullanılan, maddenin mikroyapısal ve mekanik özelliklerini geliştirmek ve modifiye etmeyi amaçlayan bir katı hal ve termomekanik işlem tekniğidir. İşlenmiş bölge modifiye edilmiş mekanik özellikler, ince taneli, eşitlenmiş ve homojen mikroyapılar içermektedir. Enerji kullanımı ve masraflarla ilgili tartışmalar, endüstrinin birçok sektöründe artmaktadır. Üretim işlemi süresince, elemanların güç tüketimi ve olası enerji tasarrufları değerlendirilebilir ve etkili enerji kullanımı için gerekli ölçüler tanımlanabilir. Bu çalışmada FSP, Al 7075-T651 alaşımlı saca uygulanmıştır. FSP’nin çok amaçlı, çok değişkenli, genel optimizasyonu bu çalışmada sunulmuştur. Hava uzay alaşımındaki çeşitli mekanik özellikler arasındaki dönüşüm ve FSP sırasındaki enerji tüketimi gözlemlenmiştir. Öncelikle, genişleme, çekme direnci, katılık, ilerleme hızı ve dönme hızı bağlamında tüketilen elektrik enerjisi ile ilgili deneysel veriler ölçülmüştür. Daha sonra, genetik optimizasyon sırasında ölçülen verileri uyumlaştırmak amacıyla, yapay sinir ağı temelli uyumlaştırma yaklaşımı kullanılmıştır. Genişleme, çekme dirence ve katılık gibi özellikler artırılırken, tüketilen elektrik enerjisinin maliyeti ise azalmaktadır. Anathar Kelimeler: Sürtünme Karıştırma İşlemi; Al7075; Çok amaçlı; Genetik Algoritma; Optimizasyon; Yapay Sinir Ağları.
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2014. Supervisor: Assist. Prof. Dr. Ghulam Hussain.
Keywords: Mechanical Engineering; Friction Stir Welding; Friction Stir Processing, Al7075, Multi-objective, Genetic Algorithm, Optimization, Artificial Neural Networks